Effect of different stages of maturity and postharvest treatments on quality and storability of pineapple - Kamol, SI; Howlader, J; Dhar, GC Sutra; Aklimuzzaman, M (Journal of the Bangladesh Agricultural University, 2016)
A study was undertaken to evaluate the effects of different maturity stages and postharvest treatments on the storage behavior of Pineapple fruits. Two distinct maturity stages viz., premature (30 days before attaining optimum maturity) and optimum mature fruits were harvested and placed in the laboratory room. On the same day six postharvest treatments viz., control, preserved in unperforated polyethylene bag, tilt, 100 ppm NAA, 200 ppm NAA, and 300 ppm NAA were assigned to that fruits. The two-factor experiment was laid out in a completely randomized design with three replications. There was significant variation between two maturity stages and among different treatments in relation to fruit characteristics. At 18 days of storage, premature fruits contained the maximum shelf-life (19.33 days), total weight loss (16.00%), moisture content (92.66%), total titratable acidity (0.77%), ascorbic acid content (17.49 mg/100g fruit) while the minimum (14.5 days), (14.67%), (90.66%), (0.68%), (9.75 mg/100g fruit) in optimum mature fruits, respectively. On the other hand, optimum mature fruits had higher dry matter content (14.78%), edible portion (67.77%), TSS (16.03%), pulp to peel ratio (2.56), total sugar content (13.5%) while these were minimum (12.57%), (65.16%), (14.43%), (2.37), (10.56%) in pre mature fruits, respectively. The fruits treated with 100 ppm NAA treatment showed the highest shelf life (22.83 days), pulp to peel ratio (2.94), total titratable acidity (0.67%), ascorbic acid content (16.78 mg/100g fruit pulp) and the lowest was in total sugar content (10.96%). Fruits treated with unperforated polythene bag gave the maximum edible portion (71.72%), moisture content (88.3%), and the minimum were in weight loss (3.42%), dry matter content (11.7%), TSS (14.68%). On the other hand, fruits with 5% tilt treatment showed the minimum total titratable acidity (0.58%) and ascorbic acid content (12.28 mg/100 g fruit pulp). Fruits with control represented the highest weight loss (19.135%), dry matter content (13.7%), total sugar content (12.75%) and the lowest were in shelf life (12.66 days), edible portion (60.098%), pulp to peel ratio (1.93). Among the treated and untreated fruits, unperforated polyethylene bag and 100 ppm NAA treatment exhibited better storage performance. J. Bangladesh Agril. Univ. 12(2): 251-260, December 2014